Management of complex liver cystic hydatidosis: challenging benign diseases for the hepatic surgeon. Issue 48 (25th November 2020) - Fancellu, Alessandro; Perra, Teresa; Vergari, Dario; Vargiu, Isabel; Feo, Claudio F.; Cossu, Maria L.; Deiana, Giulia; Porcu, Alberto
Abstract : Abstract: Hydatid cysts of the liver are benign lesions which require a wide range of surgical strategies for their treatment. We hypothesized that cysts larger than 15 cm, or compressing main vascular structures, or located in both hemilivers should be considered, as well as complicated cysts, in the category of complex hydatid cysts. In a retrospective study including 55 patients, we evaluated the characteristics of complex hydatid cysts, and compared surgical outcomes between patients operated on for complex cysts (Complex Group) and those operated on for non-complex cysts (non-Complex Group). In the Complex Group, 19% of patients had cysto-biliary communication with recurrent cholangitis, 9.5% had cysts eroding the diaphragm or chest wall, or communicating with the bronchial tree, 31% had cysts with contact with main vascular structures, 11.9% had multiple bilobar cysts, 14.3% had giant cysts with organ displacement, and 14.3% had a combination of the above-mentioned types. Type of surgical treatment was different between the two groups ( P  < .001). Additional procedures were statistically more frequent in the Complex Group ( P  = .02). Postoperative morbidity was higher in the Complex Group, although not in a significant manner ( P  = .07). Median hospital stay was longer in the Complex Group (12 vs 7 days, P  < .001). No 30-day mortality occurred. Four patients (7.3%), all belonging to the Complex Group, required reoperation for postoperative complications. Surgery for complex hydatid cysts of the liver is potentially burdened by serious complications. This kind of benign liver disease requires skill-demanding procedures and should be treated in centers with expertise in both hepato-biliary surgery and hydatid disease management. Abstract : Supplemental Digital Content is available in the text